Does behavioural economics equip policy-makers with a complete (enough) picture of the human: the case of nudging - Wincewicz-Price, Agnieszka (Journal of Public Governance, 2019)
Objectives: The article offers a critical discussion of the policy of nudging and suggests so far unexplored evaluation criteria for behavioural policy experts and practitioners. Research design: A multi-disciplinary approach is taken here to fill out the thin anthropology of homo economicus – which is shown to inform the concept of nudging – with selected aspects of human agency which are commonly discussed in moral, political and economic philosophy. The aim of this paper is twofold: 1) to outline the conceptual shortcomings of the behavioural foundations of the nudge theory as it has been originally proposed by Thaler and Sunstein; 2) to suggest several non-behavioural aspects of human agency and action which extend the original concept of nudging and should be accounted for by policy-makers in their design of nudge-like behavioural interventions. Findings: It is claimed that mere inclusion of cognitive biases and irrationalities in the behavioural approach to policy does not sufficiently extend the artificial concept of the rational agent; in particular this narrow understanding of human failure misses important aspects of the rich concept of well-being. Implications: The use of nudges requires a comprehensive knowledge of the application context. In underspecified decision contexts, choice architects need to apply more care and critical reflection in order to prevent unintended or harmful consequences of nudging. Contribution: It is rare for pragmatically oriented public policy research to focus on the philosophical concepts that inform its theory and practice. This paper is a philosophical reflection on some key elements inherent in nudging. It helps better to understand the ambiguous design, potential and limitations of nudge policy.